Atlas of Remote Sensing for World Heritage: China - Huadong, Guo. (Springer Berlin Heidelberg : Imprint: Springer, 2013)
Atlas of Remote Sensing for World Heritage: China describes the UNESCO Natural and Cultural Heritage Sites in China and focuses on the interrelationship between culture and nature as well as on the breadth and complexity of China's world heritage sites. It emphasizes the application of space technology to world heritage, offering a vivid portrayal of China's forty world heritage sites and their surrounding environments by using multi-band, multi-resolution, multi-temporal spaceborne and airborne remote sensing data and 3D models. The book is a valuable resource for researchers in fields related to world heritage and to anyone with an appreciation of natural beauty and cultural landmarks. Professor Guo Huadong is the Director-General of the Center for Earth Observation and Digital Earth, the Chinese Academy of Sciences, China.